Hubungan Pola Makan Dan Aktifitas Fisik Dengan Daya Tahan Jantung Paru Pada Anak Usia 6-9 Tahun di SD Yapis Merapi Fakfak - Irsan Yunus Woretma; Supriatna Supriatna; Yulingga Nanda Hanief (LPPM Politeknik Pratama, 2024)
This study aims to determine the relationship between diet and physical activity with heart and lung endurance of children aged 6-9 years at SD Yapis Merapi Fakfak. This research is a Quantitative Descriptive research. The population in this study were students in grades I-IV of SD Yapis Merapi Fakfak Fakfak Regency. While the sample used amounted to 30 students aged 6-9 years at the time of the TKJI measurement. The sampling technique used purposive sampling technique. Measurement of Heart and Lung Endurance is done by measuring 1 test item, which is a 600 meter run. The technique of collecting Diet and Physical Activity on Endurance using test and questionnaire methods. The results of the study obtained data that the level of Heart and Lung Power in class I-IV students of Yapis Merapi Fakfak Elementary School, Fakfak Regency, namely class I-IV students need to increase Heart and Lung Endurance because it is in the classification of less. The hypothesis of this study is H0 which reads there is no relationship between diet and physical activity with heart and lung endurance, rejected because the significant value is less than 0.05 or 0.055 <0.05, while H1 is accepted because the significant value is more than 0.05 or 0.055> 0.05 which means there is an influence of diet and physical activity with endurance. Based on the results of the product moment correlation test research with SPSS, namely 0.584 (X1) to Y and 0.453 (X2) to Y, it can be concluded that there is a sufficient relationship between diet and physical activity with endurance.